Taylor Dome Ice Core Chemistry, Ion, and Isotope Data - Smith, Jesse; Sowers, Todd A.; Brook, Edward J; Mayewski, Paul A.; Steig, Eric J.; Indermuhle, A (IEDA: US Antarctic Program Data Center, 2004)
Abstract: This data set includes chemistry, ion, and istotope data from Taylor Dome, part of the East Antarctic ice sheet. Deep drilling at Taylor Dome successfully reached bedrock at a depth of 554 meters during the 1993-1994 austral summer. The Taylor Dome ice core is only the second core (after Vostok) to provide a stratigraphically undisturbed record through the entire last glacial cycle (the last 130,000 years or more).